Comparison of two monoclonal antibody kits with cell culture isolation in the detection of respiratory virus antigens - Khairullah, N.S. (Faculty of Medicine, University of Malaya, 1996)
Two different preparations of monoclonal antibodies developed against respiratory viruses have been evaluated by the immunofluorescence antibody technique. The Chemicon monoclonal antibodies were found to be more efTicient at picking up positive specimens with a high sensitivity and specificity than Imagen monoclonal antibodies. However, the overall concordance rate of the monoclonal antibodies was 92.3%-100%. Generally, when compared with cell culture isolation, the immunofluorescence antibody technique was found to be more sensitive. The high quality of the Chemicon monoclonal antibodies contribute to their value in providing definitive diagnosis, within a few hours of specimen collection, thus allowing early management of patients, their contacts and control of hospital infection.